2016
DOI: 10.3329/jafmc.v12i2.41098
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cutaneous Adverse Drug Reactions in Bangladesh: A Review in a Tertiary Level Hospital

Abstract: Introduction: The Severe Cutaneous Adverse Drug Reactions (SCADRs) are rare but life-threatening as these encompass drug reaction with eosinophilia and systemic symptoms (DRESS), Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) and acute generalized exanthematous pustulosis (AGEP). Objective: To estimate the incidence of SCADRs and to find out the cause in Bangladesh. Materials and Methods: 50 patients with SCADRs were studied over a period of 1 year from January 2015 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…On the other hand, only 2 (28.57%, n=7) (5 victims died) victims were survived when discontinuation of the culprit drug was done after the first 48 hours of the event-detection (Table 3). (Chowdhury et al 2016). An one year long study in Bangladesh showed that among the SCADRs during that time, 46% cases are SJS, 28% cases are TEN, 16% cases are DRESS and 10% cases are AGEP recorded (Chowdhury et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, only 2 (28.57%, n=7) (5 victims died) victims were survived when discontinuation of the culprit drug was done after the first 48 hours of the event-detection (Table 3). (Chowdhury et al 2016). An one year long study in Bangladesh showed that among the SCADRs during that time, 46% cases are SJS, 28% cases are TEN, 16% cases are DRESS and 10% cases are AGEP recorded (Chowdhury et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…(Chowdhury et al 2016). An one year long study in Bangladesh showed that among the SCADRs during that time, 46% cases are SJS, 28% cases are TEN, 16% cases are DRESS and 10% cases are AGEP recorded (Chowdhury et al 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation